MATERIALS FOR PRODUCTION OF METAL MOLDS - A. Ju. Jakovlev; I. P. Volchek (Литьë и металлургия)
The influence of alloying with manganese, chromium, nickel, copper and molybdenum on mechanical characteristics and thermocyclic endurance of grayed steel and possibility of its application for metal casting molds is investigated.